KEBIJAKAN MERDEKA BELAJAR SEBAGAI LANGKAH INOVATIF DALAM PEMBANGUNAN NASIONAL - Aliyazid, Moh. Wakil; Asy’ari, Hasyim; Rizal, Syaiful (International Conference on Humanity Education and Society (ICHES), 2025)
This study discusses the policy of independent learning as a new, innovative approach in the national development process. In the era of the industrial revolution 4.0, education in Indonesia is expected to be able to adapt in a flexible and relevant way. Independent learning, which was introduced in 2019 by the Ministry of Education, Culture, Research and Technology, provides freedom to schools, teaching staff, and students in undergoing a learning process that suits their respective needs and potentials. This study adopts a literature review method with a descriptive qualitative approach, using analysis from various sources of literature and documentation and policies. The study findings indicate that independent learning can encourage improvements in the quality of human resources through a project-based learning approach, character building, and the development of relevant skills in the 21st century. However, there are still challenges faced, such as uneven facilities between regions, the readiness of educators, and understanding of the new curriculum. Therefore, the implementation of this policy needs to be supported by adequate infrastructure, training for teachers, and cooperation between sectors. In conclusion, independent learning shows significant potential as a basis for transformation in education and sustainable national development.